Trap states, electric fields, and phase segregation in mixed-halide perovskite photovoltaic devices - Knight, AJ; Patel, JB; Snaith, HJ; Johnston, MB; Herz, LM (Wiley, 2020)
Mixed-halide perovskites are essential for use in all-perovskite or perovskite–silicon tandem solar cells due to their tunable bandgap. However, trap states and halide segregation currently present the two main challenges for efficient mixed-halide perovskite technologies. Here photoluminescence techniques are used to study trap states and halide segregation in full mixed-halide perovskite photovoltaic devices. This work identifies three distinct defect species in the perovskite material: a charged, mobile defect that traps charge-carriers in the perovskite, a charge-neutral defect that induces halide segregation, and a charged, mobile defect that screens the perovskite from external electric fields. These three defects are proposed to be MA+ interstitials, crystal distortions, and halide vacancies and/or interstitials, respectively. Finally, external quantum efficiency measurements show that photoexcited charge-carriers can be extracted from the iodide-rich low-bandgap regions of the phase-segregated perovskite formed under illumination, suggesting the existence of charge-carrier percolation pathways through grain boundaries where phase-segregation may occur.